Combatting Falsification and Counterfeiting Of Medicinal Products in the European Union: A Legal Analysis - Vishv Priya Kohli (Copenhagen Business School (CBS), 2018)
The study of counterfeiting and falsification of medicinal products, from a legal perspective, is a relatively new area in the EU. Specific regulations that focus on falsification of medicines came as recently as 2011. Therefore, this discipline is also new for research. There are two primary objectives of the thesis. The first is to analyse how EU law addresses counterfeiting and falsification of medicinal products, (Directive 2011/62/EU, Directive 2004/48/EC, and Regulation 608/2013) – de lege lata. The second is to analyse whether the law containing tools to combat counterfeiting and falsification of medicinal products meets the social objectives of public health (Articles 9 and 168) and consumer protection (Articles 12 and 169), as envisaged by the Treaty on the Function of the European Union. The thesis establishes that the problem of counterfeiting and falsification of medicinal products lies at the intersection of three spheres of law - IP law, Medicine law, and Criminal law. This insight provides the foundation for the understanding of the weaknesses in the legal regime that contains tools for combatting counterfeiting and falsification of medicines in the EU.
hdl:10398/9571
Keywords: 650